2018
DOI: 10.1016/j.invent.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of internet-based interventions for depression in Indonesia

Abstract: BackgroundIn Indonesia, internet-based interventions may represent a promising strategy to reduce the mental health gap given that the level of internet usage in the country continues to increase. To check the acceptability of internet-based interventions, this study investigates factors that contribute to the use of internet-based interventions for depression in Indonesia.MethodThe survey was conducted online and had 904 participants recruited from specific social networks on mental health and general social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
18
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 33 publications
7
18
2
2
Order By: Relevance
“…Second, the severity of these symptoms was related to engagement with digital interventions. In needs assessment studies, participants were more willing to use DMHIs if their symptoms were more severe [ 38 , 53 , 62 , 71 , 81 , 82 ]. However, evaluation studies have shown that more severe symptoms hamper actual engagement with digital interventions [ 51 , 56 , 83 - 101 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the severity of these symptoms was related to engagement with digital interventions. In needs assessment studies, participants were more willing to use DMHIs if their symptoms were more severe [ 38 , 53 , 62 , 71 , 81 , 82 ]. However, evaluation studies have shown that more severe symptoms hamper actual engagement with digital interventions [ 51 , 56 , 83 - 101 ].…”
Section: Resultsmentioning
confidence: 99%
“…Beliefs refer to preexisting beliefs the user has about mental health help-seeking [ 88 ], their need for help [ 51 , 105 - 107 ], the acknowledgment of having mental health needs [ 88 ], and using technology for mental health treatment [ 38 , 93 , 108 , 109 ]. For example, preexisting beliefs of needing help for mental health needs and having a positive perception about mental health help-seeking facilitated participants’ engagement with an intervention.…”
Section: Resultsmentioning
confidence: 99%
“…An anticipated limitation of our RCT is the self-selected sample. It is possible that people who are more open towards innovative technology in general 61 and who received support prior to the loss 32 are more likely to sign up for this study, limiting the generalisability of findings emerging from this study. Due to the absence of an active control group (eg, face-to-face CBT), we are not able to test the effects of online CBT compared with an alternative treatment.…”
Section: Discussionmentioning
confidence: 96%
“…Fourth, in Indonesia, internet-based interventions for depression and anxiety are currently not available for either university students or for the general population. The first randomized control trial on internet-based behavioral activation for adult depression in Indonesia [ 25 , 26 ] showed promising results with lower symptoms at posttest assessment in favor of the intervention with minimum support by a lay counselor who did not have professional education and qualifications in mental health care. However, the intervention was tested in the general population, and thus, it remains unclear whether these interventions are also effective in university students with elevated symptoms of depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%